PENINGKATAN PENDAPATAN KELUARGA MELALUI PELATIHAN KEWIRAUSAHAAN PEREMPUAN NELAYAN DI DESA NOLLOTH KECAMATAN SAPARUA KABUPATEN MALUKU TENGAH - Sinay, Francisca Riconita; Tomasoa, Theodora Florence; Parinussa, Aryance (PAKEM : Jurnal Pengabdian Kepada Masyarakat, 2022)
Community service activities are carried out with the goal of: 1) Increasing the fulfillment of the standard of living for the welfare of coastal communities related to the existence of fish catches that are expected to be able to support the lives of group members. 2) Improve the ability of women fishermen groups to work together by incorporating them to organize their members to cooperate in accordance with mutual agreements and provisions in order to develop an independent entrepreneurial program from coastal women, and there is also a clear division of tasks in groups that is regulated and agreed upon through joint provisions, 3) Provide a coordinating production marketing platform incorporating groups of fisherwomen, as well as an inventory of the types of supporting facilities and infrastructure that would be required in fish marketing, in order to birth a pioneering joint group enterprise; and 4) Marketing can be classified into two sorts, namely catch raw materials and culinary preparations, in order to increase the objective of marketing program targets. A mentoring model and the entire process of science and technology transfer have been carried out using a pattern of training and mentoring for fisherwomen in order to achieve the program's objectives